P166 The emerging role of airway clearance techniques in the treatment of interstitial lung disease. (15th November 2016) - Skevington-Postles, L; Akers, S; George, P; Housley, G; Beadle, J; Devaraj, A; Chua, F
Abstract : Introduction: Patients with interstitial lung disease (ILD) may develop airway abnormalities as part of their underlying condition, in response to fibrotic/tractional dilatation or as a result of repeated bronchiolar infection. While current practice guidelines recommend the provision of pulmonary rehabilitation for ILD patients, no other interventions have been endorsed. We assessed the symptomatic need of patients with ILD for airway clearance techniques (ACT's) using a visual analogue scale, and whether, in those with fibrotic ILD, the presence of traction bronchiectasis was correlated with the need for ACT's. Methods: Over a 15-week period, data were prospectively collected on ILD patients who consented for detailed physiotherapy assessment and intervention. Those who reported a sensation of persistent secretion retention, frequent chest infections (>2 in 6 months) or those with pre-existing airway disease had a full clearance assessment. The radiological presence or absence of traction bronchiectasis was noted, as was evidence of other airway pathology such as bronchiolitis. Results: 30 ILD inpatients (16 females) were included in the study (Table 1 ). The commonest causes for admission were ILD staging ( n = 10) and disease deterioration requiring intravenous treatment ( n = 14). 27 patients (90%) required physiotherapy input and 11 patients (41%) required ACT's. 9 patients had positive sputum microbiology; of these, 3 were first isolates. 7 of these 9 patients had traction bronchiectasis on CT acquired within 3 months of assessment. One patient did not undergo CT. The presence of traction bronchiectasis correlated with a higher sputum microbial yield (p < 0.05) but not with a need for ACT (p > 0.05). Conclusion: Airway abnormalities are often not a principal therapeutic focus in ILD but symptoms related to mucostasis, recurrent infection and airflow limitation may be disabling. In this study, the majority of patients with positive microbiology had traction bronchiectasis. Although no firm conclusions can be drawn regarding the role of ACT's in their management, this intervention improved the yield of specimens for microbial analysis and facilitated pathogen-directed antimicrobial therapy. These findings suggest that a systematic physiotherapy approach including optimisation of airway clearance can benefit patients with parenchymal lung disease.